2004
DOI: 10.1002/elan.200302989
|View full text |Cite
|
Sign up to set email alerts
|

Realization of Rhodium Metal‐Oxide Electrode in Indifferent Electrolytes

Abstract: The pH-dependence of the stationary open-circuit potential E i¼0 st of rhodium electrode with a surface layer of anodically formed insoluble compounds has been studied in sulfate and phosphate solutions by means of cyclic voltammetry and chronopotentiometry. The range of potentials of the investigations performed has been confined to the region of rhodium electrochemical oxidation/reduction, i.e., 0.2 < E < 1.2 V (RHE) in order to prevent any possible interference of other reactions such as H 2 and O 2 evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, contrary to sulfuric acid solution, an overall increase in iridium electrode mass was observed in the course of the first four potential cycles, whereas the subsequent cycling led to mass decrease. Such behavior of Ir electrode in acid and alkaline solutions could be understood presuming that a layer of slightly soluble hydrous iridium oxides [8] is formed/reduced during the anodic/ [23,24,28,29]. Styrkas et al [30] have demonstrated that platinum group metals can be dissolved in acid solutions using an alternating current.…”
Section: Resultsmentioning
confidence: 99%
“…However, contrary to sulfuric acid solution, an overall increase in iridium electrode mass was observed in the course of the first four potential cycles, whereas the subsequent cycling led to mass decrease. Such behavior of Ir electrode in acid and alkaline solutions could be understood presuming that a layer of slightly soluble hydrous iridium oxides [8] is formed/reduced during the anodic/ [23,24,28,29]. Styrkas et al [30] have demonstrated that platinum group metals can be dissolved in acid solutions using an alternating current.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of morphological evolution and electrochemical studies, we also illustrate a tentative growth mechanism for their structural evolution through microgalvanic cell formation. These Rh nanostructures are of potential relevance to many applications such as single electron devices, fuel cell electrocatalysis, , photoelectrochemical cells, and catalysis of a variety of organic reactions , (hydrogenation, hydroformylation, and hydride transformation, etc.) as demonstrated by their enhanced electrocatalytic properties toward formaldehyde oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…An anodic peak at around 1.4 V (vs. RHE) of Rh(nP)/nC LSV polarization curve might be attributed to an oxidation process of Rh 3+ to Rh 4+ before oxygen evolution. 41 Meanwhile, the electrochemical surface areas (ECSAs) were measured by means of CV in 0.1 M KOH solution as shown in Fig. S9.…”
Section: Resultsmentioning
confidence: 99%